Policy Assessment of Roma Integration in the Bulgarian Society – Employment, Education, Healthcare and Housing - Todorov, Todor (Research Papers, 2012)
The present study’s objective is to make a characterization of the policies, aimed at integration of Roma ethnic minority in the social and economic life in Bulgaria. The focus of the study is conditioned by the fact that the integration of Roma population in the European Union, of which our country is already an inseparable part, is a significant element of the European socio-economic program with respect to the high degree of Roma social exclusion in the Community.The analysis is focused on the areas of employment, education, healthcare and housing. The strategic and institutional framework of the initiatives directed at overcoming the social isolation of Roma in the Bulgarian society at national, regional and local level, as well as the respective results achieved until the present moment are addressed.Critical assessment is made and recommendations formulated with respect to the improvement of various aspects of the government policy, including its structure, implementation and impact on the social inclusion of Roma population in the country.